Use of inverse gas chromatography for the physicochemical characterisation of a new synthesised liquid crystal: (S)-5-(2-methylbutoxy)-2-{[(4-dodecyloxyphenyl)imino]methyl}phenol - Ocak, Hale; Sakar, Dolunay; Cakar, Fatih; Cankurtaran, Ozlem; Eran, Belkis Bilgin; Karaman, Ferdane (TAYLOR & FRANCIS LTD, 2008)
A new liquid crystalline compound, i.e. (S)-5-(2-methylbutoxy)-2-{[(4-dodecyloxyphenyl)imino]methyl}phenol (MBDOPIMP), was prepared and characterised. Phase transition temperatures of MBDOPIMP were determined by polarising optical microscopy and differential scanning calorimetry. Trace amounts of ethyl acetate, butyl acetate, isobutyl acetate, hexane, heptane, octane, nonane and decane were passed through a chromatographic column loaded with MBDOPIMP coated on Chromosorb W. The retention diagrams of the solvents on MBDOPIMP were plotted using specific retention volumes at temperatures between 105 and 125C. Thermodynamic parameters, such as Flory-Huggins liquid-solvent interaction, [image omitted] , equation-of-state liquid-solvent interaction, [image omitted] , effective exchange energy, X eff, the exchange enthalpy, X 12 and exchange entropy, Q 12, were determined for the liquid crystal-solvent systems. Subsequently, the partial molar heats of sorption, H1,sorp and mixing, [image omitted] , were determined from the slopes of the plots of the logarithm of the specific retention volume, ln [image omitted] , versus 1/T and logarithm of the weight fraction activity coefficients, ln [image omitted] , versus 1/T, respectively.
Keywords: inverse gas chromatography; liquid crystal-solvent interaction; thermodynamic interaction parameter; OF-STATE THEORY; POLY(DIMETHYL SILOXANE); ENTROPY PARAMETERS; EXCHANGE ENTHALPY; SOLVENTS; COMPLEXES; ALKANES; Chemistry; Crystallography; Materials Science